Environmental Communication of the Kapuas River Clean Action by the Pontianak Young Generation - Herawati, Netty; Sunyata, Lina; Lukitowati, Suci; Magdalena Wuysang, Julia (ETHOS: Jurnal Penelitian dan Pengabdian kepada Masyarakat, 2024)
This article aims to increase the perception, experience, and communication of the young generation of Pontianak City in maintaining the cleanliness of the Kapuas River. The most considerable pollution of the river comes from household waste. River hygiene socialization often involves the people of riverside areas, as if they are the ones responsible for river cleanliness. The river cleanup action so far is also considered just ceremonial. This P.K.M. (community service) focuses on two activities: the digital campaign and the collective movement #AksiBersihSungaiKapuas. The digital campaign is carried out ten days ahead of World Environment Day. It contains education and recordings of the actual actions of Pontianak’s Young Generation. 134 digital campaigns are using the hashtag #AksiNyataBersihSungaiKapuas. Meanwhile, the Collective Movement is held on World Environment Day every June 5. A total of 2 tons of garbage was collected in the Kapuas River clean-up action. Plastic waste, water hyacinth, and household waste are the most common. The young generation of Pontianak City is not only a spectator but a subject in education and disseminating the habit of maintaining the cleanliness of the Kapuas River environment.